Animal models in burn research - Abdullahi, A. (Springer Basel, 2014)
Burn injury is a severe form of trauma affecting more than 2 million people in North America each year. Burn trauma is not a single pathophysiological event but a devastating injury that causes structural and functional deficits in numerous organ systems. Due to its complexity and the involvement of multiple organs, in vitro experiments cannot capture this complexity nor address the pathophysiology. In the past two decades, a number of burn animal models have been developed to replicate the various aspects of burn injury, to elucidate the pathophysiology, and to explore potential treatment interventions. Understanding the advantages and limitations of these animal models is essential for the design and development of treatments that are clinically relevant to humans. This review aims to highlight the common animal models of burn injury in order to provide investigators with a better understanding of the benefits and limitations of these models for translational applications. While many animal models of burn exist, we limit our discussion to the skin healing of mouse, rat, and pig. Additionally, we briefly explain hypermetabolic characteristics of burn injury and the animal model utilized to study this phenomena. Finally, we discuss the economic costs associated with each of these models in order to guide decisions of choosing the appropriate animal model for burn research. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00018-014-1612-5) contains supplementary material, which is available to authorized users.